A brief and personal history of post qualitative research: toward “post inquiry” (Práxis Educativa, 2018)
In this paper, the author explains her difficulty with the disconnect between the concepts and practices of “conventional humanist qualitative methodology” and postmodern and poststructural theories, especially the disconnect between their ontologies.  She describes her own history as an academic researcher who studied humanist qualitative methodology and post theories simultaneously but separately, illustrating the too-common separation of qualitative methodology from the epistemology and ontology with which it is entangled.  She encourages scholars to actually use the ontological critiques offered by the “posts” and to engage the new empiricisms of the ontological turn, perhaps using futural concepts as methods in post qualitative inquiry or “post inquiry.” Keywords: Post-qualitative research. Post inquiry. Ontological turn.